Structure and function of a monocarboxylate transporter homolog specific for L-lactate. (2nd November 2019) - Bosshart, Patrick D.; Kalbermatter, David; Bonetti, Sara; Fotiadis, Dimitrios
ABSTRACT: Monocarboxylate transporters play important roles in certain cancers. We have reported structures of an L -lactate-transporting solute carrier family 16 homolog with bound substrate and inhibitor. The structures show the transporter in the pharmacologically relevant outward-open conformation. Structure–function analysis provides insights into the molecular working mechanisms of ligand binding and L -lactate transport.